2009
DOI: 10.1038/sj.bjc.6605429
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and calcium-binding EGF domains 1 is frequently inactivated in ovarian cancer by aberrant promoter hypermethylation and modulates cell migration and survival

Abstract: BACKGROUND: Collagen and calcium-binding EGF domains 1 (CCBE1) is an uncharacterised gene that has down-regulated expression in breast cancer. As CCBE1 maps to 18q21.32, a region frequently exhibiting loss of heterozygosity in ovarian cancer, the aim of this study was to determine the expression and function of CCBE1 in ovarian cancer. METHODS: Expression and methylation patterns of CCBE1 were determined in ovarian cancer cell lines and primary tumours. CCBE1 contains collagen repeats and an aspartic acid/aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
1
37
2
Order By: Relevance
“…siRNA-mediated knockdown of the ECM protein CCBE1 in ovarian cancer cell lines was shown to enhanced cell migration. Accordingly CCBE1 was found frequently inactivated in ovarian cancer 61 . We found CCBE1 more than 6 times down-regulated by c-Myc in our secretome analysis (Table 1).…”
Section: Secreted Proteins Associated To the Ecmmentioning
confidence: 92%
“…siRNA-mediated knockdown of the ECM protein CCBE1 in ovarian cancer cell lines was shown to enhanced cell migration. Accordingly CCBE1 was found frequently inactivated in ovarian cancer 61 . We found CCBE1 more than 6 times down-regulated by c-Myc in our secretome analysis (Table 1).…”
Section: Secreted Proteins Associated To the Ecmmentioning
confidence: 92%
“…Methylation induced silencing of PTEN has also been frequently observed in primary epithelial ovarian carcinomas (Kurose et al, 2001). CTGF (encodes the connective tissue growth factor) (Kikuchi et al, 2007;Barbolina et al, 2009), CCBE1 (hypothesized to be involved in regulation of cell motility) (Barton et al, 2010), HIC1 (a p53 target gene) (Rathi et al, 2002), CDH13 (Makarla et al, 2005), and CDH1 (the loss of which correlates with the upregulation of matrix metalloproteinases and metastasis-promoting protein a 5integrin) (Sawada et al, 2008) act as metastasis suppressors. Caslini et al, 2006;Cai et al, 2009 3.…”
Section: Tissue Biomarkers Diagnosismentioning
confidence: 99%
“…A recent study demonstrated that apoptosis regulator MCL1 (induced myeloid leukemia cell differentiation protein Mcl-1) is targeted for degradation by FBXW7 [23]. Another candidate gene, collagen and calcium-binding EGF domains 1 (CCBE1) located on 18q21.32, is downregulated in breast and ovarian cancers [24,25]. Previous work has demonstrated that CCBE1 can cause primary generalized lymph vessel dysplasia in humans [26].…”
Section: Discussionmentioning
confidence: 96%